A Teenage Gothic American Dream: A Critical Exploration of Adolescence, Time, and Nature in Post-2010 Gothic-Horror Television Series - Speakman, Blair (Auckland University of Technology, 2023)
This Doctor of Philosophy explores adolescence, time, and nature in connection to the construction of identity in American culture in the twenty-first century in three post-2010 Gothic-horror television series, Riverdale (2017-), Teen Wolf (2011-2017), and The Chilling Adventures of Sabrina (2018-2020). The Gothic emerged as a mode of narrative representation in the Eighteenth century and has become omnipresent in a variety of popular culture texts including television. Following the proliferation of cable channels and streaming-video-on-demand services such as Netflix, the presence of Gothic-horror on television has exploded into what is, arguably, a new ‘Golden Age’. A number of post-2010 Gothic-horror television series feature ensemble casts of teenage protagonists and explore the trials and tribulations of adolescence. However, there is still limited scholarly attention on the representation of adolescent characters and cultural conceptions of time and nature in these television series. To critically examine adolescence, time, and nature in the selected television series, the project’s research questions are: 1) ‘What is the relationship between the representation of adolescent characters, time, and nature in Gothic-horror television series and the ongoing construction of identity in American culture in the twenty-first century?’; 2) ‘What do contemporary Gothic-horror television series reveal through their engagement with notions of time and their depiction of dreams, visions, and themes of nature versus urban?’ ; and 3) ‘What do contemporary Gothic-horror television series reveal through its engagement with notions of time and its depiction of dreams, visions, and themes of nature versus urban’. Thematic analysis and textual analysis are used to discuss adolescence, nature, and time in relation to a range of academic fields including the Gothic and television studies. The project explores how through the adolescent characters in Riverdale, Teen Wolf, and The Chilling Adventures of Sabrina, these series disrupt culturally constructed notions of nature and time. Specifically, the study uncovers the ways in which characters often experience distorted realities including dreams/nightmares or temporal interruptions in time. Remarkably, the project also reveals that the chosen series are preoccupied with the EcoGothic and the transformative nature of the forest setting, as well as horror of the decay of the American Dream.
Keywords: Gothic, Gothic television, television, adolescence, time, nature, Riverdale, Teen Wolf, The Chilling Adventures of Sabrina, thematic analysis, textual analysis